Pendampingan Sustainable Livelihood Berbasis Kearifan Lokal Dalam Meningkatkan Kesejahteraan Masyarakat Di Desa Rembitan - Pratama, Inka Nusamuda; Subandi, Azwar; Imam, Sadrul; Pratiwi, Yupitari Estu; Aprileana, Lady; Oktriani, Elisa (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
The sustainable livelihood assistance program in Rembitan Village aims to improve community welfare based on local wisdom. The activity stages include initial identification of socio-economic and environmental conditions of the village, preparation of activity plans based on community participation, as well as implementation of training and workshops. After the training, intensive mentoring is provided to help people apply new skills in their daily practice. The results achieved include increasing community capacity in sustainable agricultural techniques, developing better quality handicraft and traditional food products, as well as diversifying family income sources. Program evaluation shows a positive response from the community to training and mentoring activities, with indications of an increase in the local economy and awareness of the importance of sustainable natural resource management. This service activity not only succeeded in improving the economic welfare of the Rembitan Village community, but also strengthened local capacity in facing the challenges of sustainable development in the future. Keywords: sustainable livelihoods; local wisdom; well-being; economy  Abstrak: Program pendampingan sustainable livelihood di Desa Rembitan bertujuan untuk meningkatkan kesejahteraan masyarakat berbasis kearifan lokal. Tahapan awal kegiatan meliputi identifikasi kondisi sosial-ekonomi dan lingkungan Desa, penyusunan rencana kegiatan berbasis partisipasi masyarakat, serta implementasi pelatihan dan workshop. Setelah pelatihan, dilakukan pendampingan intensif untuk membantu masyarakat menerapkan keterampilan baru dalam praktiknya sehari-hari. Hasil yang dicapai meliputi peningkatan kapasitas masyarakat dalam teknik pertanian berkelanjutan, pengembangan produk kerajinan tangan dan makanan tradisional dengan kualitas yang lebih baik, serta diversifikasi sumber pendapatan keluarga. Evaluasi program menunjukkan respons yang positif dari masyarakat terhadap kegiatan pelatihan dan pendampingan, dengan indikasi peningkatan ekonomi lokal dan kesadaran akan pentingnya pengelolaan sumber daya alam secara berkelanjutan. Kegiatan pengabdian ini tidak hanya berhasil meningkatkan kesejahteraan ekonomi masyarakat Desa Rembitan, tetapi juga memperkuat kapasitas lokal dalam menghadapi tantangan pembangunan berkelanjutan dimasa mendatang. Kata kunci: sustainable livelihood; kearifan lokal; kesejahteraan; ekonomi